Low temperature photoluminescence spectroscopy studies on sputter deposited CdS/CdTe junctions and solar cells. Issue 2 (11th January 2016) - Tuteja, Mohit; Koirala, Prakash; Soares, Julio; Collins, Robert; Rockett, Angus
Abstract: Abstract : Device quality CdS/CdTe heterostructures and completed solar cells (∼12% efficient) have been studied using photoluminescence (PL) as a function of temperature and laser excitation power. The CdS/CdTe junctions were grown on transparent conducting oxide covered soda lime glass using radio frequency sputter deposition. In the current work we found that the PL spectra of sputtered and thermally evaporated CdTe absorber films share common features. It was found that the luminescence shifts from being dominated by sub-gap defect-mediated emission at lower excitation powers to near band edge excitonic emission at higher excitation powers. It was found that the presence of Cu suppresses the sub-band gap PL emissions. This effect was concluded to be due either to Cu occupying cadmium vacancies (VCd ) or forming acceptor complexes with them. This points to a potential role of Cu in eliminating sub-band gap recombination routes and hence increasing the charge separation ability of the device.